2011
DOI: 10.1007/s10709-011-9592-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurospora crassa homologue of Neuronal Calcium Sensor-1 has a role in growth, calcium stress tolerance, and ultraviolet survival

Abstract: NCU04379 gene encodes a conserved Ca(2+) and/or calmodulin binding protein that possesses a consensus signal for N-terminal myristoylation and four EF-hands, characteristics of Neuronal Calcium Sensor-1proteins. The NCU04379.2 knockout mutant shows slow growth rate, increased sensitivity to calcium and ultraviolet (UV) irradiation, and a wild-type fragment carrying NCU04379 gene complements the mutant. Therefore, NCU04379 gene has a role in growth, calcium stress tolerance, and UV survival. Crosses homozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Deletion of cse-1 in N. crassa results in a mutant that is viable, but sensitive to calcium stress and ultraviolet light, and which shows slightly impaired growth [33]. Similar to NCS-1 and Frq1p, CSE1 harbors a consensus signal for N-terminal myristoylation and four EF-hand domains (PF00036) predicted to be involved in calcium binding [32], [34], [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletion of cse-1 in N. crassa results in a mutant that is viable, but sensitive to calcium stress and ultraviolet light, and which shows slightly impaired growth [33]. Similar to NCS-1 and Frq1p, CSE1 harbors a consensus signal for N-terminal myristoylation and four EF-hand domains (PF00036) predicted to be involved in calcium binding [32], [34], [35].…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that these attributes would likely be conserved in N. crassa . We first focused on the role of calcium; the Δ cse-1 mutant shows growth sensitivity to excess calcium, as well as to calcium depletion [33]. We therefore hypothesized that calcium could be required for chemotropic interactions between N. crassa germlings, and to test this, we assayed fusion of wild-type germlings on growth medium depleted of Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…In T. reesei it was suggested that ENVOY and PDE are interconnected and in concert they regulate the light-dependent G-protein signaling pathway with cellulase production as an output pathway (619). The NCS of N. crassa shows functions in growth, calcium stress, and UV tolerance (863). In the fission yeast Schizosaccharomyces pombe, NCS is required for nutrition-independent sexual development and is involved in sporulation (864).…”
Section: Genomes Of T Reesei T Virens and T Atroviride Respectimentioning
confidence: 99%
“…Other Ca 2+ -related deletion strains present altered resistance to staurosporine, including Δ cse-1 , Δ camk-4 and Δ stk-16 . Knockout of cse-1 has been shown to lead to impaired germling communication and fusion 43, as well as increased sensitivity to UV irradiation and Ca 2+ 44. A previous study has shown that disruption of camk-4 results in benomyl resistance, while disruption of stk-16 leads to increased sensitivity to fludioxonil, sodium chloride and benomyl 45.…”
Section: Discussionmentioning
confidence: 99%